Implementasi Metode Taqdimul Qishoh dalam Meningkatkan Maharah Kalam di Lembaga Al-Wafiyah Kitab dan Bahasa Arab (AWKIBA) - Mualim Wijaya; Umar Manshur; Nurul Latifah (Mu'allim, 2022)
This study discusses the implementation of the Taqdimul Qisshoh method to increase maharah kalam at the AWKIBA institution, the purpose of this study is to describe how the implementation of the Taqdimul Qisshoh method to increase maharah kalam at the AWKIBA institution. This research is a descriptive qualitative and quantitative research. The subject of this study is the Taqdimul Qishoh method which was developed in an institution to train Arabic fluency and improve students' maharah kalam. Data collection techniques through observation, interviews and documentation, evaluation and also questionnaires. Meanwhile, data analysis follows the analysis process, namely; compilation of data, submission of data and verification or conclusions. And as for the object of this research, the students at the Al-Wafiyah Kitab and Arabic Language Institute (AWKIBA) Islamic boarding school Nrul Jadid Paiton Probolinggo. Based on the results of qualitative and quantitative research as follows: 1) the learning process using the Taqdimul Qisshoh method is more effective and has a great influence on students where they can improve speaking skills and develop thinking and imagination skills. 2) the results of the evaluation of 20 students were declared complete 100% in their mastery in storytelling. 3) based on the results of a questionnaire on 20 student responses, namely 95%, 90%, 95%, 100%, 95% and 90% stated "agree" with the implementation of the Taqdimul qishhoh method in improving Maharah Kalam. And the results of this study indicate that the application of the taqdimul qisshoh method at the AWKIBA institution is able to increase the Maharah Kalam of students.